Integrating the stress day index and an agrometeorological index to evaluate major crop waterlogging events: A cotton case study in the Middle-Lower Yangtze River - Tang Rong; Qian Long; Dong Chunyu; Wang Hui (Agricultural Water Management, 2025)
Waterlogging disasters, primarily caused by monsoon precipitation concentration and low-lying topography, seriously constrain cotton production in the middle and lower reaches of the Yangtze River (MLRYR). It is vital to evaluate the impacts of waterlogging at the regional scale. Previous works generally employed meteorological indicators directly, severely disregarding crop features—particularly the growth-stage effect. Based on our multiple-year cotton waterlogging field experiments as well as the accessible cotton waterlogging experimental research that conducted in the MLRYR, we integrated a waterlogging-impact assessment approach (stress day index) and a daily-step agro-meteorological index (SAPEI) to construct a regional waterlogging indicator called regional stress day index (RSDI). The RSDI was applied to characterize the spatial-temporal distribution of cotton waterlogging disasters as well as the yield-reducing impacts of cotton waterlogging in the MLRYR. The results showed that according to existing field experiments conducted in the MLRYR, the waterlogging sensitivity coefficients of cotton seeding, budding, flowering, and boll-opening were 0.23, 0.29, 0.36 and 0.12, respectively, demonstrating that cotton flowering was most susceptible to waterlogging. The RSDI, enhanced with a growth period sensitivity coefficient, effectively represents waterlogging intensity in the region. Over past six decades, waterlogging intensity has generally increased during cotton growth, with severe disasters in the eastern MLRYR (2010s) and western MLRYR (1990s). Waterlogging centers shifted inconsistently in the MLRYR, with extreme events showing the largest shifts. High waterlogging and yield loss occurred in the northeast, while the southwest experienced high waterlogging but less yield loss. The central region experienced less waterlogging but significant yield loss. Therefore, the priority drainage areas and drainage periods for cotton in the MLRYR were revealed and different optimal water management measures are needed for drainage crops in different regions of the MLRYR. In conclusion, this study can provide guidance for regionally evaluating cotton waterlogging disasters and developing drainage facility layout in the MLRYR, benefiting cotton adaptation to climate change and sustainable development.